RUTH PRAWER JHABVALA’S EAST INTO UPPER EAST: THE FATE OF BEING COLONY - K, Dian Fitri (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2021)
ABSTRACT This research intends to untangle the particular issues related to Orientalism. East into Upper East by Ruth Praver Jabvala displays the conflicted culture which happens to Indians. The Characters tend to act as Upper Class in Western Manner. Jabvala illustrates the difficulties of being Indian who has to approach western culture then fall in term of Orientalism. Orientalism by Edward W. Said is used as a tool to analyze this book especially to find Latent and Manifest Orientalism. This research shows that conflicted culture which happens to the characters in Jabvala’s was effected by Post Colonialism. In short, Upper East was built by the colonist. This book describes the way Indian sees their culture as given by the West.Keywords: cultural identity, east, upper east, orientalism, and postcolonialism.